Characterization of Secondary Structure and Thermal Stability by Biophysical Methods of the D-alanyl,D-alanine Ligase B Protein from Escherichia coli - Júnior, José Renato Pattaro; Caruso, Ícaro Putinhon [UNESP]; de Sá, Jéssica Maróstica [UNESP]; Mezalira, Taniara Suelen; Lima, Diego de Souza; Pilau, Eduardo Jorge; Roper, David; Fernandez, Maria Aparecida; Seixas, Flavio Augusto Vicente (Bentham Science Publishers, 2022)
Background: Peptidoglycan (PG) is a key structural component of the bacterial cell wall and interruption of its biosynthesis is a validated target for antimicrobials. Of the enzymes involved in PG biosynthesis, D-alanyl,D-alanine ligase B (DdlB) is responsible for the condensation of two alanines, forming D-Ala-D-Ala, which is required for subsequent extracellular transpeptidase crosslinking of the mature peptidoglycan polymer. Objective: We aimed at the biophysical characterization of recombinant Escherichia coli DdlB (EcDdlB), considering parameters of melting temperature (Tm), calorimetry and Van’t Hoff enthalpy changes of denaturation (U∆Hcal and ∆HU vH ), as well as characterization of elements of secondary structure at three different pHs. Methods: DdlB was overexpressed in E. coli BL21 and purified by affinity chromatography. Thermal stability and structural characteristics of the purified enzyme were analyzed by circular dichroism (CD), differential scanning calorimetry and fluorescence spectroscopy. Results: The stability of EcDdlB increased with proximity to its pI of 5.0, reaching the maximum at pH 5.4 with Tm and U∆HvH of 52.68 ºC and 484 kJ.mol-1, respectively. Deconvolutions of the CD spectra at 20 ºC showed a majority percentage of α-helix at pH 5.4 and 9.4, whereas for pH 7.4, an equal contribution of β-structures and α-helices was calculated. Thermal denaturation process of EcDdlB proved to be irreversible with an increase in β-structures that can contribute to the formation of protein aggregates. Conclusion: Such results will be useful for energy minimization of structural models aimed at virtual screening simulations, providing useful information in the search for drugs that inhibit peptidoglycan synthesis.
Keywords: bacterial cell wall; circular dichroism; D-alanine ligase; D-alanyl; differential scanning calorimetry; Escherichia coli; heterologous expression; recombinant protein